Traumatic grief in young people in Sub-Saharan Africa: a scoping review - Taggart H (Dove Medical Press, 2015)
Holly Taggart,1 Sheila Greatrex-White,2 1Mental Health Commission, CentreForum, Westminster, UK; 2School of Health Sciences, Queen's Medical Centre, University of Nottingham, Nottingham, UK Aim: To identify relevant and pertinent themes and interventions within the literature relating to childhood traumatic grief, in order to provide a sound background of evidence for further research and service development. Background: Childhood traumatic grief is caused when a significant person in a child's life dies under circumstances that they perceive to be traumatic. This can leave a child unable to return to the same level of physical and emotional functioning that he or she had prior to the death occurring. In Sub-Saharan Africa, there is an increased risk for childhood traumatic grief due to a high prevalence of orphanhood, environmental stressors, stigma, and abuse. This can have detrimental effects upon mental health. Methods: The review followed the York methodology: identifying the purpose and agreeing on the strategy beforehand; identifying relevant sources/studies; selecting the studies; charting the data; and collating, summarizing, and reporting results. Results and discussion: Interventions identified to prevent and/or manage traumatic grief included narrative exposure therapy, psychotherapy, mentoring, peer-group support, psychosocial support, a grief and loss therapy session, and memory boxes. Mental health remains neglected within service and policy development as well as in global health spending. The average amount expended on mental health services per person per year in low-income countries is less than $0.25. Only 36% of people in low income countries are covered by a mental health policy, compared with 92% in high income countries. Limitations: The sixth stage of the York methodology was omitted. Only papers written in English were included in the review. Conclusion: Childhood traumatic grief in young people is an important issue within Sub-Saharan Africa and has relevance to the global mental health agenda. Implications for nursing and health policy: With the HIV/AIDS pandemic continuing to threaten and the number of orphans estimated to rise, a number of recommendations developed from the literature are suggested. Keywords: childhood traumatic grief, HIV/AIDS, interventions, mental health, orphans, scoping review, Sub-Saharan Africa, young people